Effect of garlic (Allium sativum) supplemented diets on growth, feed utilization and survival of red tilapia (Oreochromis sp.) - Samson, J. S. (International Journal of Agricultural Technology, 2019)
The present study evaluated the effect of varying levels of garlic (Allium sativum) inclusion on the growth, feed utilization and survival of red tilapia (Oreochromis sp.). One hundred twenty red tilapias with initial average body weight of 7.36 ± 0.75 g were randomly introduced into 12 aquaria in 4 groups with 10 fish per aquarium. Treatments were fed with experimental diets for six weeks. The various levels of garlic powder (0, 1%, 1.5% and 2%) was added to commercial diet. At the end of the experiment, growth, survival rates, and feed utilization were evaluated. There was no significant difference in the growth of the fish. The highest survival rate was recorded from 1.5% garlic supplementation that showed significant difference compared to the control diet (P < 0.05). In terms of feed utilization, lowest feed conversion ratio (FCR) was recorded from 1% garlic inclusion that showed significant difference compared to the control diet (P < 0.05). This study showed that addition of 1% to 1.5% garlic powder in the diet improved the feed utilization and survival rate of red tilapia.